Rationally designed two-photon absorption compounds based on benzoxazole derivatives: structure–property relationships and bio-imaging applications. Issue 16 (6th April 2016) - Ge, Xinping; Gan, Xiaoping; Yao, Shun; Wang, Kang; Zhu, Weiju; Yu, Jianhua; Wu, Jieying; Tian, Yupeng; Zhou, Hongping
Abstract : Five rationally designed benzoxazole-based two photon absorption compounds were reported and their structure–property relationships were summarized clearly. Abstract : A new series of benzoxazole-based two-photon absorption (2PA) chromophores (T1–5 ) were synthesized and fully characterized. Among them, T1–3 are linear donor (D)–π–acceptor (A) type fluorophores with various electron-donating groups, whileT4 andT5 are multi-branched compounds stemming fromT3 . Their photophysical properties have been systematically investigated, and the two-photon absorption properties indicate that the highest 2PA cross-section ( σ 2PA ) is 2702 GM forT5 (in DMF). Structure–property relationships of the chromophores are comprehensively discussed based on their optical properties, crystal structures and density functional theory (DFT) calculations. In addition, a two-photon fluorescence cell imaging experiment demonstrates the potential bio-application ofT1–5 with good photostability and low cytotoxicity.